2012
DOI: 10.1002/jcp.22990
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Controls embryonic stem cell proliferation via store‐operated calcium entry and the nuclear factor of activated T‐cells (NFAT)

Abstract: Embryonic stem cells (ESCs) can self-renew indefinitely and differentiate into all cell lineages. Calcium is a universal second messenger which regulates a number of cellular pathways. Previous studies showed that store-operated calcium channels (SOCCs) but not voltage-operated calcium channels are present in mouse ESCs (mESCs). In this study, store-operated calcium entry (SOCE) was found to exist in mESCs using confocal microscopy. SOCC blockers lanthanum, 2-aminoethoxydiphenyl borate (2-APB) and SKF-96365 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 67 publications
2
28
0
1
Order By: Relevance
“…While the significance of this is unknown, cholesterol is, among other things, a precursor for steroid hormones such as estrogen and progesterone, and a recent report by Wong et al . links estrogen receptor signaling to embryonic stem cell proliferation and self-renewal [57]. Cholesterol is also known to play an important role in development, particularly through its role in the post-translational modification of the sonic hedgehog protein [58].…”
Section: Resultsmentioning
confidence: 99%
“…While the significance of this is unknown, cholesterol is, among other things, a precursor for steroid hormones such as estrogen and progesterone, and a recent report by Wong et al . links estrogen receptor signaling to embryonic stem cell proliferation and self-renewal [57]. Cholesterol is also known to play an important role in development, particularly through its role in the post-translational modification of the sonic hedgehog protein [58].…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is in accordance with the findings of Nunez et al [35], who showed that salicylate-induced inhibition of mitochondrial Ca 2+ uptake leads to inhibition of store-operated Ca 2+ entry (SOCE) and impairs cell proliferation in Jurkat and human colon cancer cells. In this context, it is interesting to note that a recent study demonstrated that functional SOCE is present in mESCs and that prevention of SOCE attenuates mESC proliferation, arrests cells at the G0/G1 phase, and decreases the expression of pluripotent markers [36]. Conversely, stimulation of SOCE using 17β-estradiol increases mESC proliferation [36].…”
Section: Discussionmentioning
confidence: 99%
“…2-APB is a reliable blocker of store-operated Ca2+ entry but an inconsistent inhibitor of InsP3-induced Ca2+ release, suggesting that the self-renewal property of mESCs relies on SOCE. SOCC blockers can reverse both stimulated proliferation and increased SOCE, suggesting that E2 mediates its stimulatory effect on proliferation via enhancing SOCE [1]. …”
Section: Reviewmentioning
confidence: 99%
“…According to the Autoimmune Related Diseases Association (AARDA), it is estimated that 50 million Americans have an autoimmune disease based on the National Institute of Health (NIH) epidemiology studies as well as individual patient group data from members of the National Coalition of Autoimmune Patient Groups (NCAPG). There is an increase in the prevalence of autoimmune diseases in the older age group [1-2]. It has been observed that women are affected more than men.…”
Section: Introductionmentioning
confidence: 99%